2005
DOI: 10.1021/la051493u
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Hydration of Lanthanide Ions on Binding to DNA in Aqueous Solution

Abstract: The interaction of the trivalent lanthanides Ce(III), Eu(III), and Tb(III) with sodium deoxyribonucleic acid (DNA) in aqueous solution has been studied using their luminescence spectra and decays. Complexation with DNA is indicated by changes in luminescence intensity. In the system terbium(III)-DNA, changes in luminescence with pH are suggested to be due to the protonation of phosphate groups. The degree of hydration of Tb(III) on binding to DNA is followed by luminescence lifetime measurements in water and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 77 publications
5
64
1
Order By: Relevance
“…DNA was thermally denatured to produce ss-DNA by heating at 90°C for 10 min and then cooling rapidly by injecting the sample into a beaker that is cooled by immersion into a mixture of cold ice and ethanol. Following this treatment, the DNA in aqueous solution for the EPR experiments was shown to be single stranded by differential scanning calorimetry (DSC) [32]. DNA concentration was measured by its absorbance at 260 nm, e 260 = 6600 M À1 cm À1 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…DNA was thermally denatured to produce ss-DNA by heating at 90°C for 10 min and then cooling rapidly by injecting the sample into a beaker that is cooled by immersion into a mixture of cold ice and ethanol. Following this treatment, the DNA in aqueous solution for the EPR experiments was shown to be single stranded by differential scanning calorimetry (DSC) [32]. DNA concentration was measured by its absorbance at 260 nm, e 260 = 6600 M À1 cm À1 .…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies with DNA [32], we have shown that the binding of lanthanides is strongly dependent upon pH, and that at high pH both phosphate groups and bases may be involved. Such two-site binding has previously been suggested from both luminescence [65] and 1 H NMR spectroscopy [66] Phosphorous-31 NMR spectroscopy has proved to be a powerful technique here for studying the conformation, dynamics and binding of nucleic acids in aqueous solutions [67][68][69].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Because of their spectroscopic and magnetic properties, trivalent lanthanide ions can be used as probes of the metal ions interaction with DNA. Costa et al 19 ). The fluorescence studies of these compounds were also performed to see the influence of DNA matrix.…”
mentioning
confidence: 99%